Alternate wetting and drying irrigation for rice in Bangladesh: Is it sustainable and has plant breeding something to offer?. (1st August 2013) - Price, Adam H.; Norton, Gareth J.; Salt, David E.; Ebenhoeh, Oliver; Meharg, Andrew A.; Meharg, Caroline; Islam, M. Rafiqul; Sarma, Ramen N.; Dasgupta, Tapash; Ismail, Abdelbagi M.; McNally, Kenneth L.; Zhang, Hao; et al.
Abstract: The crop management practice of alternate wetting and drying (AWD) is being promoted by IRRI and the national research and extension program in Bangladesh and other parts of the world as a water‐saving irrigation practice that reduces the environmental impact of dry season rice production through decreased water usage, and potentially increases yield. Evidence is growing that AWD will dramatically reduce the concentration of arsenic in harvested rice grains conferring a third major advantage over permanently flooded dry season rice production. AWD may also increase the concentration of essential dietary micronutrients in the grain. However, three crucial aspects of AWD irrigation require further investigation. First, why is yield generally altered in AWD? Second, is AWD sustainable economically (viability of farmers' livelihoods) and environmentally (aquifer water table heights) over long‐term use? Third, are current cultivars optimized for this irrigation system? This paper describes a multidisciplinary research project that could be conceived which would answer these questions by combining advanced soil biogeochemistry with crop physiology, genomics, and systems biology. The description attempts to show how the breakthroughs in next generation sequencing could be exploited to better utilize local collections of germplasm and identify the molecular mechanisms underlying biological adaptation to the environment within the context of soil chemistry and plant physiology. Abstract : The article describes the technique of alternate wetting and drying (AWD) which is being promoted in Bangladesh as a water saving technique for dry season rice production. It highlights the unknown aspects of the adoption of the method which relate to its effectiveness in the long term. Finally it reports an innovative multi‐disciplinary project which aims to examine sustainability and offer solutions through genomics, soil biogeochemistry, plant physiology and systems biology.